let X be non empty set ; :: thesis: for f, g, h being Function of X,COMPLEX
for F, G, H being Point of st f = F & g = G & h = H holds
( H = F - G iff for x being Element of X holds h . x = (f . x) - (g . x) )

let f, g, h be Function of X,COMPLEX; :: thesis: for F, G, H being Point of st f = F & g = G & h = H holds
( H = F - G iff for x being Element of X holds h . x = (f . x) - (g . x) )

let F, G, H be Point of ; :: thesis: ( f = F & g = G & h = H implies ( H = F - G iff for x being Element of X holds h . x = (f . x) - (g . x) ) )
assume A1: ( f = F & g = G & h = H ) ; :: thesis: ( H = F - G iff for x being Element of X holds h . x = (f . x) - (g . x) )
A2: now :: thesis: ( ( for x being Element of X holds h . x = (f . x) - (g . x) ) implies F - G = H )
assume A3: for x being Element of X holds h . x = (f . x) - (g . x) ; :: thesis: F - G = H
now :: thesis: for x being Element of X holds (h . x) + (g . x) = f . x
let x be Element of X; :: thesis: (h . x) + (g . x) = f . x
h . x = (f . x) - (g . x) by A3;
hence (h . x) + (g . x) = f . x ; :: thesis: verum
end;
then F = H + G by ;
then F - G = H + (G - G) by RLVECT_1:def 3;
then F - G = H + by RLVECT_1:15;
hence F - G = H by RLVECT_1:4; :: thesis: verum
end;
now :: thesis: ( H = F - G implies for x being Element of X holds h . x = (f . x) - (g . x) )
assume H = F - G ; :: thesis: for x being Element of X holds h . x = (f . x) - (g . x)
then H + G = F - (G - G) by RLVECT_1:29;
then H + G = F - by RLVECT_1:15;
then A4: H + G = F by RLVECT_1:13;
now :: thesis: for x being Element of X holds (f . x) - (g . x) = h . x
let x be Element of X; :: thesis: (f . x) - (g . x) = h . x
f . x = (h . x) + (g . x) by A1, A4, Th22;
hence (f . x) - (g . x) = h . x ; :: thesis: verum
end;
hence for x being Element of X holds h . x = (f . x) - (g . x) ; :: thesis: verum
end;
hence ( H = F - G iff for x being Element of X holds h . x = (f . x) - (g . x) ) by A2; :: thesis: verum